القروض البنكیة الاستثماریة دعم مالي للمؤسسات الصغیرة والمتوسطة د ا رسة حالة بنك الفلاحة والتنمیة الریفیة – وكالة تیسمسیلت – - radouane, adelle (Finance and Business Economies Review, 2018)
Small and medium enterprises (SMEs) mainly dependent to investment activity, in order to ensure its continuity and position in market. Through the expansion, renovation and development of its structures, equipment, and investment properties. However, when its undertaking an investment activity, in often face the insufficient financial private resources. That’s forcing them to find an external financial support, which is often provided by banks, through granting investment bank loans, in order to finance its investment activity. So in this research paper, Entitled "Investment Banking Loans Financial Support to Small and Medium Enterprises", we will try to shed light on the investment bank loans which are granting by banks as financial support for small and medium enterprises, With the case study of the bank (bank of agriculture and rural development -Agency Tissemsilt -).